Some Hormonal And Hematological Changes Accompanied With Type 2 Diabetes Mellitus: Beberapa Perubahan Hormonal dan Hematologi yang Disertai dengan Diabetes Melitus Tipe 2 - Hamza, Duaa Hamad (Indonesian Journal on Health Science and Medicine, 2025)
The goal of this research to examine the alterations in a few and hormonal and hematological markers that took place in persons with type 2 diabetes Mellitus T2DM. The current research is being conducted at the Al-Hussein Hospital's diabetes and endocrinology center in the province of Al-Muthanna. There were 200 participants in the study: 100 were T2DM patients and 100 were controls. Patients and controls ranged in age from 24 to 50. In this study, spectrophotometry was used to assess fasting blood sugar (FBS) at 546 nm, the Sysmax-Kx-21 was used to measure hematological parameters (RBC, Hb, RDW, WBC, PLT, and MPV), and the ELSA technique was used to detect hormones (TSH, T3, and T4).The FBS of T2DM patients is considerably upper than that of control patients (P<0.05), according to the results. However, the findings indicate that patients with T2MD had meaningfully lower ranks of TSH, T3, and T4 when paralleled to the control grouping. Hematological parameter data indicate that patients with T2DM had significantly lower RBC and Hb when paralleled to the control grouping, but considerably upper RDW, WBC, PLT, and MPV (P<0.05) when paralleled to the control grouping. Highlights: Higher FBS in T2DM patients compared to healthy controls. Lower TSH, T3, T4 in T2DM group than controls. Altered blood markers: Low RBC, Hb; high RDW, WBC, PLT, MPV. Keywords: T2DM , Hormones , Blood parameters